2007
DOI: 10.1103/physrevlett.99.097206
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cu Dilution in IrMn on the Exchange Bias ofCoFe/IrMnBilayers

Abstract: The effect of nonmagnetic dilution in metallic antiferromagnets (AFMs) on the exchange bias (EB) has been investigated from a structural, magnetic, and Monte Carlo simulation point of view in bilayers of CoFe/(IrMn)1-xCux. Dilution by Cu atoms throughout the volume of the AFM IrMn gives rise to an enhanced EB field (HEB) for 5 K Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 18 publications
0
39
4
Order By: Relevance
“…5). This result shows that the rotatable and frozen spins distribute uniformly inside the entire CoO film, supporting the doping and FM/AFM/FM results [25][26][27][28][29] that the exchange bias depends on the bulk AFM spin structure. It should be mentioned that the NiO spins are much softer than CoO spins due to a much weaker NiO magnetic anisotropy [37].…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…5). This result shows that the rotatable and frozen spins distribute uniformly inside the entire CoO film, supporting the doping and FM/AFM/FM results [25][26][27][28][29] that the exchange bias depends on the bulk AFM spin structure. It should be mentioned that the NiO spins are much softer than CoO spins due to a much weaker NiO magnetic anisotropy [37].…”
mentioning
confidence: 67%
“…The result shows clearly a correlation between the FM and the AFM domains, and the existence of a small amount of uncompensated spins in the AFM layer [19]. It was further shown that only a small percentage of the uncompensated spins is pinned to account for the exchange bias [20,21,22,23] and that these pinned uncompensated AFM spins actually extend into the AFM layer [24], suggesting a bulk-like effect of the AFM spins in the exchange bias [25,26,27,28,29]. Despite the above progress, the compensated AFM spin behavior remains unclear during the FM layer reversal.…”
mentioning
confidence: 81%
“…Concerning the grain measurement, different techniques are possible, including rocking curves of x-ray diffraction measurements [12,15], Transmission Electron Microscopy grid scans [11] and AFM measurements [14,16]. We preferred the last method because it is the only one that allows considering grain size distributions deposited on a Si/SiO 2 substrate.…”
Section: Methodology Of the Studymentioning
confidence: 99%
“…NSMM is an effective method for characterization of materials, including quantitative dielectric permittivity, [3][4][5][6] sheet resistance or conductivity, 7-10 ferroelectric polarization, 11 permeability 12, 13 and other properties. 14 In this manuscript, we present how the map of high frequency conductivity distribution of an oxide-doped ferromagnetic 19,20 200 nm thin film can be obtained from the quality factor (Q) measured by NSMM. In our calculations, circuit analog approximation was used to determine the electrical properties of the resonator used in NSMM.…”
Section: Introductionmentioning
confidence: 99%